Analisis Hubungan Antara Tingkat Pendidikan Dan Perilaku Berisiko Dengan Angka Kejadian Demam Berdarah Dengue (DBD) Di Desa Mayangrejo - Putra, Anak Agung Sagung Ayu Saraswati; Arini, Shintia Yunita; Lusno, Muhammad Farid Dimjati; Ardyanto w, Denny; Irwanto, Bian Shabri Putri; Syafi'i, Imam; Fadli, Rino Choirul; Rokhman, Arifatur (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Dengue hemorrhagic fever emerges in tropical countries like Indonesia. Bojonegoro is one of the highest districts with increased cases in East Java. The high incidence of dengue hemorrhagic fever in Bojonegoro is riveting to be explored related to some causative factors, including education and community behavior. Moreover, education affects an individual level of knowledge, which will impact a person's behavior that potentially affects the public health degree, especially the incidence of dengue hemorrhagic fever. This study aimed to determine the relationship between education and risky behavior in dengue hemorrhagic fever incidence in Mayangrejo Village, Bojonegoro Regency, East Java. A cross-sectional approach was used within a total population of 302 participants, and the Lemeshow sampling technique reached 67 respondents. Data were collected using a questionnaire distributed to residents' homes, while the Fisher's Exact Test was used for data analysis. The results showed a significant relationship between behavior and the incidence of dengue hemorrhagic fever (p-value = 0.024), and there was a relationship between education level and the incidence of the disease (p-value = 0.022). Performing health education and undertaking one House one Jumantik program is then recommended.